Pengaruh Cash Turnover, Loan to Deposit Ratio, Capit al Adequacy Ratio, dan Dana Pihak Ketiga terhadap Profitabilitas LPD - Sujana, Putu Cahyadi; Mustanda, I Ketut (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2015)
The  purpose of  this  study  was  to  determine  the  effect  of   cash  turnover ,  loan  to  deposit  ratio,   capi tal adequacy rat io,  and  third-party  funds  to  the profi tabil ity  of  Lembaga  Perkreditan  Desa  (LPD)  in  Denpasar  2010-2012. Thi s study  used observasion  method is to study and look at the  financial statements of  the LPD  period 2010-2012  and  found  a  sample  of   34  LPD.  This  study  found  that  the  cash  turnover ,  loan  to  deposit  ratio  and  capi tal adequacy  rat io  by  part ial  signi ficant  positive  effect  on  the  profitability  of  LPD  in  Denpasar  2010-2012. Meanwhile,  third-party funds  significant negat ive effect   on  the  profitabili ty of   LPD in Denpasar  2010-2012.
Keywords: cash turnover, loan to deposi t rat io, capital adequacy ratio, third-party funds, profitability